Optimizing the Performance of the PSHS CARC Knowledge Hub: A Mixed-Method Evaluation of a Moodle-Based LMS - Cuyasen, Graceson (The Indonesian Journal of Computer Science, 2025)
Abstract—This study focuses on optimizing the performance of the Philippine Science High School – Cordillera Administrative Region Campus Knowledge Hub (PSHS-CARC KHub), a Moodle-based Learning Management System (LMS), by addressing key performance issues such as slow response times. A mixed-method approach, including a comprehensive literature review and experimental testing, was used to identify effective strategies for hardware, software, and front-end optimization. The study examined the impact of server configurations, memory upgrades, and Apache module optimizations on system performance. Results indicate that hardware optimizations (such as SSD deployment), software improvements (including database indexing and caching), and front-end enhancements (such as minimizing HTTP requests and optimizing images) led to measurable improvements in system scalability and responsiveness. While performance tests showed reduced response times and stable throughput, occasional delays for high-latency transactions were observed. These findings provide actionable insights for optimizing Moodle-based LMS platforms, improving both user experience and system efficiency.